Application of TOPSIS method for optimization of process parameters in robotic deburring. (2020) - Leo Princely, F.; Senthil, P.; Selvaraj, T.
Abstract: Robotic deburring has emerged as an important finishing process in manufacturing, which mainly improves the functional aspects of the machined product. Before deburring a product, it is imperative to select the proper deburring tool and to fix appropriate deburring parameters to optimise the process. This article details the deburring experiments conducted on aluminium workpieces under various deburring conditions based on L18 standard Orthogonal Array (OA). A set of input parameters such as deburring wheel diameter, tool rotational speed and tool feed rate were chosen to yield a lower deburring force and surface finish values. Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methodology was applied to ascertain the optimum deburring parameters with an objective of surface roughness and deburring force minimisation. The result disclosed that the suggested technique is capable of solving multi-criterion optimisation of the deburring parameters.